Management of Activities of the Rospotrebnadzor Institutions in the Khabarovsk Territory with the View to Sanitary-Epidemiological Welfare Provision for the Population in the Period of High Water - V. A. Ott; T. A. Zaitseva; T. N. Karavyanskaya; Yu. A. Garbuz; O. E. Trotsenko (Проблемы особо опасных инфекций, 2014)
In order to enhance the surveillance over sanitary-epidemiological situation in the period of flood, 2013 Rospotrebnadzor institutions in the Khabarovsk Territory took anti-epidemic team augmentation, affiliated to Irkutsk Research Anti-Plague Institute. Moreover, forged have been 30 mobile units for investigation of sanitary conditions in the residential areas of the region, water supply and water-consuming facilities, quality of nutrition among the population, living and sanitary conditions in the temporal accommodation sites; 11 mobile groups for sample collecting from ambient environment objects. Carried out has been operational deployment of two laboratory sub-units with the following membership: 5 microbiological, 5 sanitary-chemical, 2 radiological and 1 virusological facilities. By efforts of Rospotrebnadzor institutions performed has been a complex of key sanitary-hygienic, anti-epidemic and prophylactic measures aimed at prevention and control over distribution of mass infectious diseases, at the provision of sanitary-epidemiological welfare of the population in the Khabarovsk Territory, and the relief of social tension during the period of rainfall floods in August-September, 2013.